1999
DOI: 10.1046/j.1365-2028.1999.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and survival of suricates (Suricata suricatta) in the southern Kalahari

Abstract: SummaryIn most respects, the demography of Kalahari suricates (Suricata suricatta) resembles that of other social mongooses. Average group size varies from four to nine, and groups typically include several mature females, of which one is responsible for the majority of breeding attempts. Breeding females show a postpartum oestrus; gestation is around 60 days; litter size is three to five pups at emergence and females rarely breed before the age of 24 months. In contrast, annual survival rates (0.20 for pups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
1
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 21 publications
4
100
1
3
Order By: Relevance
“…Both study areas experienced a hot, wet summer (October^April), followed by a cold, dry winter (May^September) (Mills 1990). Breeding occurred most frequently during the summer months (November^March) but, over the ¢ve years of the study, births were observed in all months of the year (Clutton-Brock et al 1999a). For the purpose of these analyses, we de¢ned the breeding season as the period between 1 September and 31 March.…”
Section: Methodsmentioning
confidence: 99%
“…Both study areas experienced a hot, wet summer (October^April), followed by a cold, dry winter (May^September) (Mills 1990). Breeding occurred most frequently during the summer months (November^March) but, over the ¢ve years of the study, births were observed in all months of the year (Clutton-Brock et al 1999a). For the purpose of these analyses, we de¢ned the breeding season as the period between 1 September and 31 March.…”
Section: Methodsmentioning
confidence: 99%
“…We used averages when multiple values for a given parameter for a given species were available. Data on annual adult survival were collected from reviews [26][27][28], and we searched for additional survival values from the primary literature specifically to increase the sample of cooperative breeders [29][30][31]. Continuous variables were log-transformed prior to analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Data on survival, fecundity, and emigration behavior of meerkats have been extensively analyzed and are presented elsewhere (e.g., Clutton-Brock et al 1999a, 1999b, 2001bRussell et al 2002Russell et al , 2003a. We analyzed the current data set specifically to provide the parameters necessary for our dispersal model.…”
Section: Model Parameterizationmentioning
confidence: 99%
“…Details of the habitat and climate during the study period are provided elsewhere (Clutton-Brock et al 1999b;. Up to 28 groups were identified during the study period (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001), but for the life-history data presented below, only data from the 14 most intensively studied groups were used.…”
Section: Study Speciesmentioning
confidence: 99%